Serotyping of Streptococcus pneumoniae strains by coagglutination. - Smart, L E (1986)
The coagglutination test, which uses staphylococcal protein A, for serotyping strains of Streptococcus pneumoniae, was extended to include serotyping within serogroups. Serotyping was performed with "factor sera" prepared in the laboratory. Fifty one strains of S pneumoniae, which belonged to one of the seven serogroups included in the 14 valent vaccine formulation, were tested, and no inconsistency was found when compared with the capsule swelling reaction.